Predation behavior of Ceraeochrysa cincta (Schneider, 1851) (Neuroptera: Chrysopidae) on eggs parasitized by Trichogramma galloi Zucchi, 1988 (Hymenoptera: Trichogrammatidae) - Pimenta, Isabela C. de O.; Guarnieri, Carlos C. de O.; Barros, Thiago N. de; Ramalho, Dagmara G.; De Bortoli, Sergio A. (BioAssay, 2025)
Biological control consists of regulating pest species populations through the release of natural enemies, which are often produced in the laboratory and can be carried out by more than one species of biocontrol agent. In the case of the association of two or more of these agents, studies are necessary to understand the interaction between them; as a result, additive and noncompetitive control actions can be applied in biological control. The objective of this study was to evaluate the predation behavior of Ceraeochrysa cincta (Schneider, 1851) (Neuroptera: Chrysopidae) on eggs of its alternative prey, Corcyra cephalonica (Stainton, 1865) (Lepidoptera: Pyralidae), parasitized by Trichogramma galloi Zucchi, 1988 (Hymenoptera: Trichogrammatidae). Preference tests (free- and no-choice) were carried out, where it was observed that the first- and third-instar larvae of the predator preferred to feed on unparasitized eggs, whereas second-instar larvae preferred parasitized eggs. The results suggest that the variation in predatory behavior of C. cincta among instars may affect its compatibility with T. galloi, representing a relevant factor in the development of integrated biological control strategies.